UPAYA PEMBINAAN MUALAF DALAM MENINGKATKAN PEMAHAMAN KEISLAMAN DI DUSUN NGGERUKOPA DESA PALAMA - Rahma, Rahma; Syarifuddin, Syarifuddin; Missouri, Randita (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Mualaf often face internal problems, such as confusion in identity change and feelings of isolation from the social environment, as well as external problems, such as lack of support from family and the surrounding community. So this research aims to find out the Efforts of Mualaf Development in Improving Islamic Understanding in Nggerukopa Hamlet, Palama Village, Donggo District, Bima Regency. This research will be conducted in Nggerukopa Hamlet, Palama Village, Donggo Subdistrict, Bima Regency, West Nusa Tenggara. This research uses Qualitative Research with a Case Study Approach. Data Collection Techniques are Observation, Interview and Documentation. Data Analysis Techniques are Data Reduction, Data Presentation and Conclusion Drawing. Based on the results of the research conducted, it can be concluded that the efforts of coaching converts in Nggerukopa Hamlet have been carried out quite well and structured. This coaching is focused on increasing Islamic understanding through activities such as routine recitation, individual coaching, and guidance on worship and morals